Form and Structure in Ancient Poetry, I-II - Kosmala, H. (1977)
< VT 14 (1964) 423-445; 16 (1966) 152-180; Hebrew and Ugaritic verse consists of parallel lines of an equal number of ‘thought-units’, not beats or stresses.